Lessons From APOL1 Animal Models - Yoshida, Teruhiko; Latt, Khun Zaw; Heymann, Jurgen; Kopp, Jeffrey B. (Frontiers in Medicine, 2021)
African-Americans have a three-fold higher rate of chronic kidney disease compared to European-Americans. Much of this excess risk is attributed to genetic variants in APOL1, encoding apolipoprotein L1, that are present only in individuals with sub-Saharan ancestry. Although ten years have passed since the discovery of APOL1 renal risk variants, the mechanisms by which APOL1 risk allele gene products damage glomerular cells remain incompletely understood. Many mechanisms have been reported in cell culture models, but few have been demonstrated to be active in transgenic models. In this narrative review, we will review existing APOL1 transgenic models, from flies to fish to mice; discuss findings and limitations from studies; and consider future research directions.